Normative values of the mitral valve apparatus: a 3D multicenter WASE study exploring age and sex differences. (4th February 2022) - Henry, M; Cotella, JI; Mor-Avi, V; Investigators, WASE
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The mitral valve (MV) is a complex and dynamic structure that can be best evaluated by 3D imaging. Recent advances in mitral percutaneous interventions have escalated the need for a more quantitative and comprehensive assessment of the MV. Understanding normal valve size, structure and function is essential for differentiation of healthy from disease states. Purpose: Using data from the World Alliance of Societies of Echocardiography (WASE) normal values study, we aimed to determine how normative values for the MV apparatus vary across ages and sexes. Methods: 3D full volume data sets obtained with transthoracic echocardiography in 618 normal subjects (50% male) were analyzed using commercial MV analysis software (TOMTEC) to determine annular and leaflet dimensions and areas (Figure). The subjects were divided into groups by sex (301 men and 311 women) and by age: 18-40 years (N = 211), 41-65 years (N = 201) and >65 years (N = 206) to identify sex- and age-related differences. Inter- and intra-observer variability was assessed in a subset of 30 subjects and expressed as mean absolute difference between pairs of repeated measurements. Results: Compared to women, men had larger annular dimensions in both the anterior-posterior and anterolateral-posteromedial planes, as well as larger annular circumference and area, larger tenting size parameters, and larger leaflet length and area (Table, bottom left). Age-related differences in multiple parameters were statistically significant (Table, bottom right). Of note, sex- and age-related differences in most MV parameters were comparable to or smaller than the corresponding measurement variability (Table, top right). Conclusion: This analysis of the WASE data provides normative values of the mitral apparatus size and morphology for male and female subjects. While sex- and age-related differences were noted, they need to be interpreted with caution in view of the associated measurement variability.